Polipropileno reciclado para contato com alimento: etching e deposição de filmes de carbono amorfo hidrogenado por plasma - Paiva, Robert da Silva (Universidade Federal de São Carlos, 2020)
The increasing applications of polymers make this material one of the most consumed in the world market. Accompanying this scenario is the generation of waste, and although plastic has gradually conquered its space as a material of great importance to current society, its disposal is still a problem for the world and especially for Brazil, due to the lack of proper management of solid urban waste (MSW). Among thermoplastic resins, polypropylene (PP) is the one that presents the greatest consumption growth in the last years, which is related to its versatility and good processability, besides its relative low cost. Despite these characteristics, PP still has limited properties, especially in applications that require high barrier properties and transparency, such as food packaging. The use of recycled materials for food contact has some restrictions regulated by international agencies such as the Food and Drugs Administration (FDA) in the USA, European Union directives and the National Health Surveillance Agency (ANVISA) in Brazil. Many studies have been conducted to verify the occurrence of migration of contaminants from these recycled packaging destined to come into contact with food. One of the techniques used to improve barrier properties is surface coating with thin films. This type of deposition can be done by the technique called Plasma Enhanced Chemical Vapor Deposition (PECVD), obtaining hydrogenated amorphous carbon (a-C:H) films deposited on the recycled material. In this work, PP pellets were submitted to a forced contamination protocol, simulating the worst conditions for consumer use of food packaging. Then, contaminated PP went through a process of washing, drying, reprocessing and thermopressing to obtain PP films. The films were exposed to etching plasma surface treatment of oxygen gas, argon and atmospheric air in 2.5 and 5 minutes to increase surface adhesion. Contact angle measurements were performed and surface tension was determined. Morphological changes were determined by atomic force microscopy (AFM), and the chemical modification was evaluated by X-ray (XPS) and FTIR-ATR photoelectron spectroscopy, proving the formation of oxygen and nitrogen based groups. In addition, the a-C:H films were characterized by Raman that proved the majority structure of the PLC type and, the thickness of the films were measured by profiling, allowing the production of films of 100, 300 and 500 nm. The samples were submitted to contact with food simulant liquids and contaminant migration tests, followed by extraction and analysis by SPME-GC-MS, allowing the evaluation of the potential increase in barrier property of these materials. In addition, SEM were made of the films, before and after the migration tests in order to analyze the micro cracks and defects caused by the tests. The results indicate that the migration of contaminants is related to the type of simulant, functional film thickness, as well as the presence of micro effects. However, a-C:H films are a good alternative for the coating of recycled polymers for application in the food area.
Recycled food contact polypropylene: etching and deposition of hydrogenated amorphous carbon films by plasma
Keywords: Polipropileno; PECVD; Embalagens de alimento; Migração de contaminantes; Filmes de carbono amorfo hidrogenado; Polypropylene; Food packaging; Contaminant migration; Hydrogenated amorphous carbon films; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA